Economic Growth, Wages and Education Levels on Labor Absorption in Districts/Cities in South Sulawesi Province - Hamka, Hamka; Fitrianti, Retno; Yakub, Andryirawan; Sopian, Andi; Sapanang, A. Baso Aditya; Fitrianti, A. Nur (Asian Journal of Management Analytics, 2024)
An analysis of the impact of economic growth, wages, and education levels  on workforce absorption in the regencies and cities of South Sulawesi. The objective of this study is to examine the impact of economic growth, wages, and education level on workforce absorption in regions with low unemployment rates. Additionally, it aims to investigate the influence of economic growth, wages, and education level on employment absorption in regions with high unemployment rates. Furthermore, the study will analyze the sectoral elasticity of the workforce in both low and high unemployment regional groups. This study employs a Panel Regression of Random Effect Model with a Generalized Least Square (GLS) Approach and Elasticity using a five-year panel data from 24 regencies and cities in South Sulawesi. The findings indicate that in the regional group with low unemployment, wages have a positive and significant impact on workforce absorption, while the level of education has a negative and significant impact. In the regional group with high unemployment, both economic growth and educational level have a positive and significant impact on workforce absorption. Additionally, the agricultural sector exhibits the highest workforce elasticity in the regional group with low unemployment, while the trade sector shows high elasticity in the regional group with high unemployment.